Current Study of Nonformal Education Program in The Era of The Industrial Revolution 4.0 - Iis Prasetyo; Entoh Tohani; Moses Adeleke Adeoye (Journal of Nonformal Education, 2024)
The development of information technology encourages the formation of lifestyle, the ability to learn innovation, and the development of technology-oriented life skills education. This condition has an impact on improving the qualifications of non-formal educators both academically and in other competencies. This study aims to produce a theoretical analysis of the development of non-formal education in the era of the Industrial Revolution 4.0 and describe the latest non-formal education programs in accordance with the needs of the Industrial Revolution era 4.0 post-pandemic. This study employed a qualitative approach with a systematic review method. Through this approach, the researcher summarized the primary research result to present a more comprehensive and balanced fact by applying 8 stages of systematic review research. Collecting data was conducted through a document review process with a data collection tool in the form of a review guideline table. The research analysis used was a meta-aggregation technique. The results show that there has been a paradigm shift in the philosophy of non-formal education leading to progressive education, which is marked by efforts to improve skills, accompanied by good and literate behavior. Technological developments encourage changes in non-formal education practices, learning activities, and the substance and output of learning programs. This research presents novel learning models, alternative credentials, and adaptive tactics to effectively tackle the problems and seize the benefits of a future dominated by technology, therefore making it very pertinent and optimistic.